The Haskalah community of Zgierz based on Sefer Zgierz, Mazkeretnetsach Le-Kehilayehudit Be-Polin - Kucner, Monika; Gołaszewski, Marcin (Acta Universitatis Lodziensis. Folia Germanica, 2023)
The Haskalah, as an intellectual movement among Jews, was a reformist trend of the late 18th century. In Zgierz, it only emerged in the 1860s. Its goal was to promote a new cultural ideal of the Jew as someone well-versed in the Torah while simultaneously integrating into the local community. Education, combating Jewish separatism, preserving identity, culture, and the Hebrew language, as well as the languages of local communities, were key tasks undertaken by the maskilim. Jewish Enlightenment was also manifested through active involvement in local government institutions, interactions with the Christian population, literary and journalistic activities. The following article attempts to outline the specific characteristics of this phenomenon in Zgierz, depicting its history, significance, and development.